The effectiveness of international conventions in the struggle against world’s domestic violence - Andrusiak, Iryna; Mykievych, Mykhailo M.; Harasymiv, Taras Z.; Chornopyska, Viktoiya Z.; Oliinyk, Yaryna (Jurnal Cita Hukum, 2024)
The issue of the spread of domestic violence is an urgent challenge to the modern legal system, which is regulated in particular by the adoption of international conventions. The research aim is to investigate the effectiveness of international conventions in combating domestic violence. Implementing the specified aim is based on the comparative analysis of specialised scientific literature, the use of content analysis and abstraction methods. The results show that the existing international conventions demonstrate their effectiveness if they are used in combination with other legal instruments for combating domestic violence. The main regulatory mechanisms for protection against domestic violence are restricted in the Convention on the Elimination of All Forms of Discrimination against Women and the Istanbul Convention. Separate international normative acts constitute an essential basis that became the foundation for the formation of relevant provisions in the systems of national legislation, which is especially noticeable in the examples of democratic EU countries. However, in the countries of Asia and Africa, there are critical indicators of domestic violence, which can also be explained by the fact that local governments have not ratified the relevant conventions. The conclusions emphasise that for the further effective implementation of international conventions and their integration into national legislation, it is essential that different groups of the population are aware of their provisions.